2022
DOI: 10.20517/jca.2022.16
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide: the gas that fuels longevity

Abstract: The molecular determinants of lifespan can be examined in animal models with the long-term objective of applying what is learned to the development of strategies to enhance longevity in humans. Here, we comment on a recent publication examining the molecular mechanisms that determine lifespan in worms, Caenorhabditis elegans (C. elegans), where it was shown that inhibiting protein synthesis increased levels of the transcription factor, ATF4. Gene expression analyses showed that ATF4 increased the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…[188] Studies using various model organisms have shown that decreased protein synthesis, decreased translation, and increased fidelity of protein synthesis slow aging and extend lifespan. [226,124,227,34,131] Signaling pathways involved in CLS extension also influence translational regulation. For example, the TOR and PKA pathways regulate ribosomal gene transcription in S. cerevisiae.…”
Section: Prostaglandin Jmentioning
confidence: 99%
See 2 more Smart Citations
“…[188] Studies using various model organisms have shown that decreased protein synthesis, decreased translation, and increased fidelity of protein synthesis slow aging and extend lifespan. [226,124,227,34,131] Signaling pathways involved in CLS extension also influence translational regulation. For example, the TOR and PKA pathways regulate ribosomal gene transcription in S. cerevisiae.…”
Section: Prostaglandin Jmentioning
confidence: 99%
“…[130] Therefore, daf-16 may be required for lifespan extension by H 2 S. Furthermore, H 2 S is reportedly important for extending the lifespan of nematodes by inhibiting TORC1 or protein translation. [124,131] In addition, H 2 S is involved in the aging of mammals. [132][133][134]…”
Section: Hydrogen Sulfidementioning
confidence: 99%
See 1 more Smart Citation